Glyceria spicata subsp. onubensis (Gramineae), nuevo taxón para la flora ibérica - López Martínez, Josefa; Devesa Alcaraz, Juan Antonio (Acta Botanica Malacitana, 2019)
Glyceria spicata subsp. onubensis (Gramineae), new taxon for the iberian flora Palabras claves: Glyceria, Gramineae, Península Ibérica, Taxonomía. Key words: Glyceria, Gramineae, Iberian Peninsula, Taxonomy.